Progressive Systemic Sclerosis with Interstitial Lung Disease Post Radio Ablation in Graves Disease's Patient: A Case Report - Maha Chakri Willheljulya; Sumartini Dewi; Andri Reza (Indonesian Journal of Rheumatology, 2022)
Systemic sclerosis (SSc) is a connective tissue disease marked by degenerative microvascular abnormalities and immune system activation, resulting in skin and internal organ fibrosis. The link between thyroid problems and systemic sclerosis is unknown. Although several studies have demonstrated that patients with systemic sclerosis develop Graves' illness as the condition progresses, only a few have reported that Graves' patients develop progressive systemic sclerosis. It is an uncommon instance of multiple autoimmune illnesses in which SSc develops gradually after the birth of the first child and the patient had Graves' disease since the age of 17 and had thyroid ablation 5 years ago. SSc illness has a characteristic clinical appearance, involving the skin to the rest of the body and internal organs, particularly the lungs.